Dynamic Calculation of the Pile Supported Wharf - Iegupov, Konstantin; Meltsov, Gennady; Iegupov, Vyacheslav; Bezushko, Denys (Academic journal Industrial Machine Building Civil Engineering, 2018)
The article deals with the issues of designing and operating marine pile supported wharf in the seismically hazard areas considering various superstructures and overload equipment influence. Analysis of hydraulic structures seismic resistance erected in seismic regions of Ukraine shows that the actual seismic load on buildings significantly exceeds the estimated loads that are determined by the normative documents before 2006. Design of hydraulic structures should be done considering berths of reloading complexes, with proper scientific support. Berth construction calculationsof the ship repair yard No. 2 of the «Ilichevsk Ship Repair Plan» are given.